Health and happiness of older Korean women participating in dance activities. Issue 3 (March 2023) - Han, Jee-Hoon; Sa, Hye Ji
Abstract: This study aimed to determine the health and happiness of older women participating in dance activities using the phenomenological analysis method. The study used snowball sampling to recruit eight participants among older women participating in a 3-month dance program in Korea, starting from March 2019. Data were collected through in-depth interviews and participatory observations, after which the gathered raw data were codified, systematically arranged, and analysed. The contents were then categorized by topic or content into different categories to derive meaningful interpretations and research results. To enhance the reliability and validity of the analysis, objectivity was ensured by applying appropriate criteria for assessing qualitative research. The analysis determined the participants' motivations for participation, health satisfaction, and happiness. The results conclusively and theoretically confirm the importance of dance-induced feelings of health and happiness among the older women in the study. The results should encourage relevant government agencies and other organizations to put increased effort into enacting policy measures to promote older women's health by revitalizing their participation in dance activities and providing them with long-term recreational interventions. Highlights: We study the health and happiness of older Korean women in a dance program. Our phenomenological analysis draws on participant interviews and observations. We codify, arranged, and analyse the data, and categorize them by topic or content. We identify motivation for participation, health satisfaction, and happiness. The results confirm the importance of dance-induced feelings of health and happiness.